جرائم الحرب وجرائم العدوان في فقه محكمة العدل الدولية - مسلم نبراس ابراهيم (Journal of Legal Sciences, 2017)
We had, in this research, the role of international justice in the development of legal principles for war crimes and aggression (ICJ model), where divided by the two sections: the first, outlining the role of international justice in the development of legal principles concerning war crimes. The second section, dedicate to indicate the role of international justice in the development of the crime of aggression and legal principles. In conclusion we mentioned the most important conclusions we reached in this regard, and some of the necessary recommendations in this area.